If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + x) = 17 + x (3 * 3 + x * 3) = 17 + x (9 + 3x) = 17 + x Solving 9 + 3x = 17 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 3x + -1x = 17 + x + -1x Combine like terms: 3x + -1x = 2x 9 + 2x = 17 + x + -1x Combine like terms: x + -1x = 0 9 + 2x = 17 + 0 9 + 2x = 17 Add '-9' to each side of the equation. 9 + -9 + 2x = 17 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 17 + -9 2x = 17 + -9 Combine like terms: 17 + -9 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 16v^2-8v+1= | | 6s-20=4+8s | | y=10+-4x | | 4x+2x=108 | | y+2/8=y-2/7 | | x^6*x= | | x+2x+(x+17)=129 | | 3s-17=-7+5s | | x/4+4/7 | | -5(x+11)+365=19+16 | | 3x+3=17+x | | 2x+2x=100 | | 3t-15=60+8t | | 7p/5+p=12 | | log^2(x^2-6x-23)=2 | | (w^2+w-20)(w^2+11w+30)3+(w^2+2w-24)(w^2+11w+30)1=(w^2+2w-24)(w^2+w-20)3 | | 4x^2+29x-30=0 | | (w^2+w-20)(w^2+11w+30)3+(w^2+2w+24)(w^2+11w+30)1=(w^2+2w-24)(w^2+w-20)3 | | 2-3(2x-1)=2 | | 5(3+4x)-2=33 | | 8x-3=11+6x | | 3x+7(4x-12)=133 | | 3x+3x=144 | | 2v^2+3=-7v | | y^2+18xy+81x^2= | | 1/2x-1/3(x-8)=3x | | 3x+5(x-7)=5 | | 5x+(-13y)+(-x)+11y= | | 2x+5(x+2)=80 | | 8=3(3-x) | | r-17=-33 | | 2x+2x+2x=69 |